1996
DOI: 10.1002/aic.690420121
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and correlation of ion activity in aqueous single electrolyte solutions

Abstract: Ion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 16 publications
2
78
1
2
Order By: Relevance
“…The basic question is: 'Are the ionic activity coefficients measurable as claimed by us (Khoshkbarchi and Vera, 1996;Wilczek-Vera et al, 2004, 2010Wilczek-Vera and Vera, 2009a) and also by other researchers (Shatkay and Lerman, 1969;Lee et al, 2002;Schneider et al, 2003Schneider et al, , 2004Zhuo et al, 2008) or, as claimed by Malatesta (2009Malatesta ( , 2010 the real values are still unknown?' The term 'real' is used here in the sense of the actual value of the physical property, the value that can be used for chemical engineering design.…”
Section: General Considerations On the Measurability Of Activitiesmentioning
confidence: 96%
“…The basic question is: 'Are the ionic activity coefficients measurable as claimed by us (Khoshkbarchi and Vera, 1996;Wilczek-Vera et al, 2004, 2010Wilczek-Vera and Vera, 2009a) and also by other researchers (Shatkay and Lerman, 1969;Lee et al, 2002;Schneider et al, 2003Schneider et al, , 2004Zhuo et al, 2008) or, as claimed by Malatesta (2009Malatesta ( , 2010 the real values are still unknown?' The term 'real' is used here in the sense of the actual value of the physical property, the value that can be used for chemical engineering design.…”
Section: General Considerations On the Measurability Of Activitiesmentioning
confidence: 96%
“…In this convention, the emf sign is obtained by subtracting the potential of the element to the left from the potential of the element to the right, with the schematics of the cell as written. In the first publication of the senior author on the subject of the activity of ions (Khoshkbarchi and Vera, 1996a), the Henderson equation for the junction potential (Henderson, 1907(Henderson, , 1908 was used in the form given in the text of Bates (1965), and the equation for the cell was taken from the text of Skoog and Leary (1992) as…”
Section: Reference Electrodementioning
confidence: 99%
“…We will not repeat the arguments here, but the interested reader can find in recent literature (Malatesta, 2006a;Wilczek-Vera et al, 2006a) all details and pertinent references of previous discussions on the subject. Although independent measurements in other laboratories (Lee et al, 2002;Schneider et al, 2003Schneider et al, , 2004 have confirmed the repeatability of results obtained by the method proposed by Khoshkbarchi and Vera (1996) to measure individual ionic activities, it may be argued that the same biased assumptions were used in all cases. This work presents innovative experiments designed to provide independent tests of the method to measure the activity of individual ions.…”
Section: Introductionmentioning
confidence: 89%
“…In these experiments it was noticed that the emf readings of the cation ISE measured against the anion ISE gave the same result as the difference of the ISE's individual readings against the single junction reference electrode (Kakabadse, 1981;Haghtalab and Vera, 1991a,b). This non-trivial observation suggested the possibility of measuring the activities of single ions and the method was developed for this purpose (Khoshkbarchi and Vera, 1996). The activity of individual ions was a property believed by many to be impossible to measure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation